Clarification of sugar palm sap using a pilot scale microfiltration - Ritthipairote, Tapanee; Youravong, Wirote; Meenun, Mutita; Wanichapichart, Pikul (2004)
It is known that microfiltration can be used for clarification and cold sterilization of beverage and drink products. In this study the sugar palm sap was clarified using a pilot scale of crossflow microfiltration system. The membrane used was tubular ceramic membrane (ZrO2-TiO2) with pore size 0.1 and 0.2 Âµm. The experiments were carried out with batch mode at constant crossflow velocity 3.5 m.s-1 and 50 Â°C. It was found that the turbidity and number of microorganism in the permeate for both membrane pore size were reduced greatly while total soluble solid did not significantly decreased. The permeate flux behavior and fouling were also investigated. The permeate flux decreased greatly with processing time due to membrane fouling. The irreversible fouling of both membrane pore size also increased greatly indicating that the irreversible fouling was a major cause of fouling.